Star-planet interactions and selection effects from planet detection methods - Poppenhaeger, K.; Schmitt, J.H.M.M. (Astronomische Nachrichten, 2011)
Planets may have effects on their host stars by tidal or magnetic interaction. Such star‐planet interactions are thought to enhance the activity level of the host star. However, stellar activity also affects the sensitivity of planet detection methods. Samples of planet‐hosting stars which are investigated for such star‐planet interactions are therefore subject to strong selection effects which need to be taken into account (© 2011 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)